قضايا المجتمع الجزائري في صحافة الجمعية العلماء المسلمين الجزائريين (1931- 1954) - زينب بن سعيدان; د/ محمد يزير (جامعة عمار ثليجي الاغواط, 2023)
الملخص : لقد أقرت الجمعية العلماء المسلمين منذ بداية تأسيسها في 05 ماي 1931، برأسها الشيخ الحميد إبن باديس على أن نشاطها الإجتماعي محض، وأن السياسة بعيدة عن مجال إهتماماتها، ولم يمضي وقت طويل على تأسيسها حتى وجدت نفسها مضطرة للخروج عن قانونها بتحريم السياسة، فكانت تضطر في كثير من الأحيان إلى تعبير عن مواقفها السياسية في كل مرة تصدر فيها فرنسا قرارا تمس فيها المجتمع الجزائري في مختلف جوانب حياته، وواضح عن بعدها السياسي في مجالها الإصلاحي. وسخرت الجمعية كامل جهدها لدعم الثورة التي قام بها أبناء الوطن سواء من الخارج وذلك من خلال مجهودات الشيخ البشير الإبراهيمي والشيخ مبارك الميلي والشيخ عبد الحميد إبن باديس في الدول العربية والإسلامية وإسماع صوت الثورة الجزائرية، وذلك من خلال المشاركة في المؤتمرات واللقاءات، وداخليا من خلال صحف والجرائد الجمعية وخصوصا البصائر التي واكبت أحداث الثورة من البداية إلى مختلف الظروف التي مرت بها وكانت جرائدها أهم الأحداث السياسية والإجتماعية والدينية، وكذا فضح الأساليب الإستعمارية الرامية إلى مسخ الهوية الجزائرية بفرنسا وتنصيرها ومتابعة جميع أنشطة الجمعية والعناية بالشبيبة الجزائرية وحمايتها من الإستعمار ومؤسساته . Absrtract : Since the beginning of its founding on May 5, 1931, the Association of Muslim Scholars, leader by Sheikh Al-Hamid Ibn Badis, it has acknowledged that its activity is purely social, and that politics is far from the field of its interests.It was not long after its founding that it found itself forced to deviate from its law by prohibiting politics, so it was often forced to express its political positions every time France issued a decision affecting Algerian society in various aspects of its life. It is clear about its political dimension in its reform field. The association harnessed all its efforts to support the revolution carried out by the countrymen, whether from abroad, through the efforts of Sheikh Al-Bashir Al-Ibrahimi, Sheikh Mubarak Al-Maili and Sheikh Abdul Hamid Ibn Badis in the Arab and Islamic countries, and to make the voice of the Algerian revolution heard through participation in conferences and meetings.Also, internally through the newspapers of the association, especially Al-Basair, which accompanied the events of the revolution from the beginning to the various circumstances that it went through. Its newspapers were the most important political, social and religious events, as well as exposing the colonial methods aimed at deforming the Algerian identity in France and Christianizing it, following up all the activities of the association and taking care of the Algerian youth and protecting them from colonialism and its institutions.